2000
DOI: 10.1029/2000jd900121
|View full text |Cite
|
Sign up to set email alerts
|

Modeled Arctic ozone depletion in winter 1997/1998 and comparison with previous winters

Abstract: Abstract.We have used a three-dimensional stratospheric model to investigate 1996/1997, the mean difference is negative and the amplitude is less than 15%. In winter 1995/1996 the mean difference is negative and the amplitude reaches 43%.The differences in 1995/1996 and 1996/1997 result despite good agreement between model and observations in midwinter, and they develop following the large chemical losses which occurred in those winters. We suggest that a major contribution to the model/observation difference… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
36
1

Year Published

2000
2000
2013
2013

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 41 publications
(7 reference statements)
3
36
1
Order By: Relevance
“…Some of these also appear to overestimate the chemical loss during warm winters (e.g. Guirlet et al, 2000). Previous studies also indicate that current CTMs cannot give a satisfactory observed partial column ozone loss (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Some of these also appear to overestimate the chemical loss during warm winters (e.g. Guirlet et al, 2000). Previous studies also indicate that current CTMs cannot give a satisfactory observed partial column ozone loss (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…However, the effects of some specific reactions remain unclear and need to be further investigated as polar ozone losses determined with different climate-chemistry models show significant differences as discussed in Chapter 6 of SPARC CCMVal (2010) and references therein. Several studies quantified the chemical ozone loss in the Arctic polar vortex using a variety of techniques and instruments (e.g., Chipperfield et al, 1996;Goutail et al, 1997;Deniel et al, 1998;Rex et al, 1999;Becker et al, 2000;Guirlet et al, 2000;Eichmann et al, 2002;Grooß and Müller, 2003;Goutail et al, 2005;El Amraoui et al, 2008). The methods employed to quantify the chemical ozone loss include, e.g., (1) the match technique (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of attention placed on ozone loss in the polar regions, numerous theoretical models routinely underestimate ozone loss rates in much of the lower polar stratosphere (between about 400 and 550 K) compared to "observed" loss rates (e.g., Chipperfield et al, 1996;Goutail et al, 1997;Deniel et al, 1998;Becker et al, 2000;Guirlet et al, 2000). Even with the most recent Arctic field campaign results (e.g., SOLVE I/II, the SAGE III Ozone Loss and Validation Experiment; THESEO-2000, the Third European Stratospheric Experiment on Ozone; and VINTERSOL, Validation of International Satellites and Ozone Loss) this long-standing problem has yet to be resolved (e.g., Pierce et al, 2003).…”
Section: Introduction and Objectivesmentioning
confidence: 99%
“…As mentioned by Guirlet et al (2000) and Harris et al (2002), quantitative comparisons of the different ozone loss calculations can be difficult since each method considers different altitudes, time periods, and area averages of the vortex. When comparing ozone loss results it is critical to understand these differences as well as the weaknesses of each method.…”
Section: Introduction and Objectivesmentioning
confidence: 99%